Evolution of Esophageal Motility Testing: From Kronecker to Clouse. Issue 3 (September 2021) - Grubic, Andrew D.; Crookes, Peter F.
Esophageal motility, the science of quantifying the mechanical function of the esophagus, was initiated by Hugo Kronecker in Germany in 1882. Little progress was made until after World War II, when motility studies began in the Mayo Clinic and Boston University. After 1960, several key figures promoted the science, including Lauran Harris, Don Castell, Jerry Dodds, Tom DeMeester, Peter Kahrilas, and Ray Clouse. All were inspirational teachers and mentors as well as scientists. The technical developments from balloons and perfused catheters to the current solid-state catheters and sophisticated software has provided insights which have helped physicians to treat patients with dysfunction of the esophagus with increasing success.